Evil and the hiddenness of God - Rea, Michael (Australia CENGAGE Learning, 2015)
Offers a collection of essays to draw students into this robust and enduring philosophical topic.
Preface. Historical and Literary Perspectives. 1. The Argument from Evil. David Hume. 2. Theodicy: A Defense of Theism. Gottfried Leibniz. 3. Rebellion. Fyodor Dostoevsky. 4. The Ones Who Walk Away from Omelas. Ursula K. LeGuin. The Problems of Evil and Divine Hiddenness. 5. Evil and Omnipotence. J. L. Mackie. 6. The Inductive Argument from Evil against the Existence of God. William Rowe. 7. Evolution and the Problem of Evil. Paul Draper. 8. Whose Problem is the Problem of Evil? Grace Jantzen. 9. Divine Hiddenness Justifies Atheism. J. L. Schellenberg. Responses. 10. The Free Will Defense. Alvin Plantinga. 11. Evil and Soul-Making. John Hick. 12. Epistemic Humility, Arguments from Evil, and Moral Skepticism. Daniel Howard-Snyder. 13. The Problem of Evil and the Desires of the Heart. Eleonore Stump. 14. Horrendous Evils and the Goodness of God. Marilyn McCord Adams. 15. Suffering as Religious Experience. Laura Waddell Ekstrom. 16. Deus Absconditus. Michael J. Murray. 17. Divine Hiddenness, Divine Silence. Michael Rea. Index.
Keywords: Theodicy; Good and evil; Good and evil -- Philosophy